MYTH TO MARGIN: PERFORMATIVE VISUAL NARRATIVES AND THE DRAMATICS OF FEMALE CHARACTERIZATION IN MALAYALAM CINEMA - Manavalan, Amala; D, Deepa Caroline (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Contemporary Malayalam cinema occupies a unique generative position in the Indian regional film industry, specifically in its negotiation of feminist subjectivity and visual dramatics of characterizing women. The present paper analyses three recent Malayalam films, Lokah Chapter 1: Chandra (2025), Ekō (2025), and Rekhachithram (2025), as sites of particular performative discourse of womanhood being enacted, choreographed, and contested. Drawing on Judith Butler’s theory of gender performativity, Laura Mulvey’s concept of the male gaze, and Erving Goffman’s dramaturgical model, the paper argues that these films do not merely reflect feminist subjectivity but actively produce it: the visual and dramatic modes of expressing femininity are not given but rather produced, contested, and reformulated through a carefully crafted visual grammar. The three films are interpreted as occupying three distinct dramaturgical spaces- the front stage of spectacular mythological reclamation (Lokah), the back stage of withheld domestic power (Ekō), and the off stage of posthumous reconstruction (Rekhachithram)- which together trace a trajectory from myth to margin around which contemporary Malayalam cinema choreographs its feminist visual turn. This discussion contributes to the growing body of literature on feminist film theory in regional, non-Western cinema and demonstrates the analytical utility of applying performativity theory, gaze theory, and dramaturgical analysis as a combined framework to the study of female characterization in Indian cinema. The findings indicate that the post-Hema Committee moment in Malayalam cinema has produced not only a political discourse within the film industry but a tangible and formal change in the visual grammar of female characterization—one in which performance as the dramatics of the body itself becomes the locus of feminist intervention.